Determinan Perilaku Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri di SMA Se-Kota Kalabahi, Kabupaten Alor - Ataupah, Mira Kiliana; Weraman, Pius; Sir, Amelya Betsalonia (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
There are many causes of death for women n this world, one of which s breast cancer. Breast cancer s the second largest contributor to the death rate for women after cervical cancer. This disease s a condition where cells n the breast grow rapidly and attack all parts of the body. However, only a small proportion of women perform BSE, namely 25 to 30% of young women who do BSE. This study aims to analyze the determinants of breast self-examination (BSE) behavior n female adolescents at high schools n Kalabahi City, Alor Regency. This research s a quantitative study using a cross sectional study design method. The sample n this study were all young women attending high schools n Kalabahi City, Alor Regency, namely 312 young women. The data analysis used n this study was univariate analysis and bivariate analysis, using the chi-square test with a significant level of 95% (α = 0.05). The results showed that there was a significant relationship between knowledge (ρ-value = 0.000), attitude (ρ-value=0.000), nformation exposure (ρ-value=0.000), family history (ρ-value=0.000), and peer support (ρ-value=0.000) with BSE behavior. Young women are expected to be able to play an active role and have the willingness to seek nformation related to BSE and do so according to the right steps. Schools and health offices are expected to be a source of nformation for young women regarding BSE through various health promotion efforts, especially counseling or socialization related to BSE.